Targeting complex plutonium oxides by combining crystal chemical reasoning with density-functional theory calculations: the quaternary plutonium oxide Cs2PuSi6O15. Issue 66 (20th July 2020) - Pace, Kristen A.; Klepov, Vladislav V.; Christian, Matthew S.; Morrison, Gregory; Deason, Travis K.; Kutahyali Aslani, Ceren; Besmann, Theodore M.; Diprete, David P.; Amoroso, Jake W.; zur Loye, Hans-Conrad
Abstract : The stability of the novel Pu(iv ) silicate, Cs2 PuSi6 O15, was predicted from a combination of crystal chemical reasoning and DFT calculations and confirmed by its synthesis via flux crystal growth. Abstract : The stability of the novel Pu(iv ) silicate, Cs2 PuSi6 O15, was predicted from a combination of crystal chemical reasoning and DFT calculations and confirmed by its synthesis via flux crystal growth. Formation enthalpies of the A2 MSi6 O15 (A = Na–Cs; M = Ce, Th, U–Pu) compositional family were calculated and indicated the Cs-containing phases should preferentially form in the Cmc 21 structure type, consistent with previous experimental findings and the novel phases produced in this work, Cs2 PuSi6 O15 and Cs2 CeSi6 O15 . The formation enthalpies of a second set of compositions, A2 MSi3 O9, were also calculated and a comparison between the two compositional families correctly predicted A2 MSi6 O15 to be on average more stable than A2 MSi3 O9 .